Ural Officials in the District Town of the First Half of the 1870s (Diary of a Servant of the Ural Landowners Golubtsov) - M. B. Larionova (Научный диалог, 2021)
The features of the formation of the appearance of a provincial district society are analyzed on the example of the Ural district town of Krasnoufimsk, Perm province. The factors that influenced the changes taking place in the bureaucratic environment in the first half of the 1870s are considered, the composition of Krasnoufimsk district officials is presented. The study was carried out on the basis of data recorded by the former serf of the Perm landowners Golubtsovs Matvey Andreev in the published Diary. Through the eyes of a representative of a different class, some aspects of the relationship between the Krasnoufimsk bureaucratic district society and the representative of the upper noble class V. P. Golubtsov (1832—1887) are shown. It is indicated that the information contained in the Diary testifies to the changes taking place in society associated with the erosion of its composition and the weakening of the influence of officials in the space of the county town, when the content component of the previously formed traditions changes by introducing new models of behavior by representatives of other classes. The relevance of the study is seen in the importance of studying the socio-cultural space of the provincial city in general and the Ural in particular, which had its own specific features that influenced the formation of urban society. It is concluded that although only some socio-cultural aspects of the life of a provincial society are shown, their identification and study will help to better understand what important processes took place in society during the post-reform period.